Control de calidad de un embutido artesanal jamón de pescado a partir de polydactylus approximans guapuro - Viñan Saraguro, Verónica Elizabeth (2013)
The present work was carried out in the laboratory of Technology and Processing of Aquatic Organisms, Faculty of Agricultural Sciences of the University of Machala is the following aims: To determine the qualitative characteristics of fish ham. The variable that is analyzed in this paper was: analysis as moisture, ash, protein, pH. At the end of this research we can conclude the following: The pulp processed ham Guapuro presented the qualitative characteristics of moisture, protein, fat and ash similar to those obtained by previous researchers but this research is called the formulation A certificate for human consumption and lower percentage of fat present, because in his formulation of fewer added pork. The guapuro is a raw material that has nutritional properties with soft white flesh fish odor and low commercial value, and which could favor their use in the preparation of meats for human consumption. Sensory evaluation showed a favorable acceptance for ham with fish in both formulations. Is recommended to determine the useful life of the various formulations of fish ham considering different storage temperatures and evaluate the feasibility of marketing the fish ham, considering production costs.